2021
DOI: 10.1111/jcpe.13575
|View full text |Cite
|
Sign up to set email alerts
|

One‐year outcomes of dental implants with a hybrid surface macro‐design placed in patients with history of periodontitis: A randomized clinical trial

Abstract: Aim: To evaluate the radiological, clinical, and microbiological outcomes of implants with a hybrid surface macro-design in patients with a history of periodontitis. Material and Methods:The study was designed as a 12-month, parallel-arm, randomized controlled trial where patients with a history of treated periodontitis in need of dental implants for single-unit or short-span prosthesis were randomly allocated to a test [implants with a machined titanium surface in the coronal collar (hybrid; HS)] or a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In a retrospective study in patients with a history of periodontitis, a hybrid surface, i.e., presenting a turned surface limited to the coronal part and the remaining portion of the implant with a rough surface, showed less marginal bone loss compared to a conventional rough surface [ 23 ]. However, no clinical, radiographic, and microbiological differences were found between hybrid and traditional implants in a randomized clinical trial (RCT) in patients with history of periodontitis [ 24 ]. Even though a turned surface presented high clinical results when installed in pristine alveolar bone [ 19 ], the conditions for osseointegration might be compromised by the presence of regenerated composite bone, composed of newly formed bone and residual graft particles.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study in patients with a history of periodontitis, a hybrid surface, i.e., presenting a turned surface limited to the coronal part and the remaining portion of the implant with a rough surface, showed less marginal bone loss compared to a conventional rough surface [ 23 ]. However, no clinical, radiographic, and microbiological differences were found between hybrid and traditional implants in a randomized clinical trial (RCT) in patients with history of periodontitis [ 24 ]. Even though a turned surface presented high clinical results when installed in pristine alveolar bone [ 19 ], the conditions for osseointegration might be compromised by the presence of regenerated composite bone, composed of newly formed bone and residual graft particles.…”
Section: Introductionmentioning
confidence: 99%
“…Another option to reduce the risk of an exposed microrough surface to the peri-implant sulcus is the utilization of a socalled hybrid design (HD) implant (Tarnow, 1993). A HD implant has by definition a micro-rough surface in the endo-osseous portion for improved bone anchorage, and a machined surface in the neck/ shoulder area for the trans-and supracrestal area to reduce the risk for biofilm colonization, and hence the development of biologic complications over time (Monje et al, 2021;Serrano et al, 2022) The essence and inspiration of all HD implants is the tissue-level implant by Straumann first utilized in 1986 (Sutter et al, 1988). Long-term studies seem to document the increased risk for peri-implantitis for non-HD implants, when the micro-rough is exposed to the supracrestal area (Derks et al, 2016;Windael et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent biologic complications because of the exposure of the rough surface secondary to bone loss, the use of one-piece implant designs (such as tissue level implants), hybrid implant surfaces, and the subcrestal placement of implants have been proposed. [150][151][152][153][154][155] To minimize the initial bone remodeling associated with vertical ridge augmentation procedures, a second protecting layer of bone grafting at the time of implant placement has also been advocated. 146 Results using a mixture of a slowly resorbable xenogenic bone graft and autogenous bone chips covered with a resorbable membrane demonstrated that epi-crestally placed implants into vertically augmented bone exhibited excellent marginal bone stability.…”
Section: Long -Term Outcome S Of Vertic Al Ridg E Aug Mentation Proce...mentioning
confidence: 99%
“…In this context, implant design and surface characteristics may play a role. To prevent biologic complications because of the exposure of the rough surface secondary to bone loss, the use of one‐piece implant designs (such as tissue level implants), hybrid implant surfaces, and the subcrestal placement of implants have been proposed 150–155 …”
Section: Long‐term Outcomes Of Vertical Ridge Augmentation Proceduresmentioning
confidence: 99%